Contamination patterns and molluscan and polychaete assemblages in two Persian (Arabian) Gulf oilfields. (7th June 2016) - Albano, Paolo G.; Filippova, Nadezhda; Steger, Jan; Schmidbaur, Hannah; Tomašových, Adam; Stachowitsch, Michael; Zuschin, Martin
Abstract: This study examined two shallow‐water, offshore oil facilities and their surroundings in the Umm Al Dalkh and Zakum oilfields [United Arab Emirates, Persian (Arabian) Gulf]. The focus was on sediment contamination levels and the detection of disturbance based on two representative invertebrate components of the benthos: molluscs and polychaetes. We tested the hypothesis that significant disturbance to the community has occurred, by examining whether distance from the platform or variation in contaminants explains among‐site variation in the composition of benthic communities. Moreover, we also tested the hypothesis that organic enrichment because of oil input has modified the feeding guild structure by examining whether the relative abundances of filter‐feeders, deposit‐feeders and omnivores are correlated with distance from the platform or with contamination by hydrocarbons. The contamination levels and their spatial distribution in the sediments differed significantly between the two fields, as did their mollusc and polychaete communities. The within‐field variability, however, was much lower: no clear structuring of contamination values and species composition and abundance was detectable in relation to distance from the oil platform. Contamination levels were low, often below detection levels or international guideline values. Variation in contaminant concentrations did not explain variation in taxonomic composition and abundance. The relative abundance of the above‐mentioned feeding guilds did not correlate with either distance from the platform or with contaminant concentrations. These patterns may reflect the long time that has elapsed since drilling (15–20 years), which appears to have allowed contaminants to disperse and degrade and assemblages to recover from the impact, if indeed such a disturbance ever occurred. In contrast to low values of barium and total petroleum hydrocarbons, associated with well drilling, some metals were at their highest concentrations beneath the central platforms. This suggests that production‐related activities (including platform cleaning and maintenance) are currently a more relevant contamination source.